(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper introduces a Theoretical Market Framework (TMF) for conceptualizing and designing electricity markets, integrating Transmission System Operator And Distribution System Operator (TSO–DSO) coordination mechanisms.